Pengaruh Penyuluhan Kesehatan Melalui Media Video Terhadap Upaya Pencegahan Penyakit Skabies di Pesantren IMMIM Putra Makassar - Endang Sri Mulyawati Liambana; Nur Juliana; Firnasrudin Rahim (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
The high prevalence of skabies in Islamic boarding schools is due to the limited knowledge, attitudes and behavior. The prevalence of school age suffering from scabies is 64%. The aimed of study was the effect of health education through video of media on efforts to prevent skabies at the Islamic Boarding School IMMIM Putra Makassar. The type of research used is pre-experimental design with a one-group pre-test and post-test design. Samples was 50 respondents using purposive sampling technique consisting of class VIII and IX. Collecting data used was questionnaire. The data were analyzed with wilcoxon test. The results of the pre-test knowledge category 54,0%, low 46,0%, post-test knowledge was high 98.0% and low 2,00%. Pre-test attitude positive 90,0%, negative 10,0%, while the post-test positive attitude 96,0% and negative 4,00%. The pre-test for the category behavior is quite 100,0% while the post-test for the category action is quite 100,0%. The results of p value <0.05 means that there is an effect of health counseling using video media on knowledge (0.000) attitudes (0.000) and behavior (0.002) to santri in an effort to prevent skabies disease. It is hoped that the management of the pesantren can prohibit students from exchanging clothes and beds so that the transmission of skabies does not occur, conduct mass treatment to break the chain of disease, for santri to improve environmental of quality, clean and healthy living on behavior.